The Birth Prevalence of Cleft Lip and/or Cleft Palate After the 2011 Tōhoku Earthquake and Tsunami. (October 2019) - Imai, Yoshimichi; Sanada, Takehiko; Tachi, Masahiro
Objective: This study examined whether the 2011 Tōhoku earthquake and tsunami affected the birth prevalence of cleft lip and/or cleft palate (CL/P) in Miyagi Prefecture, where the earthquake and tsunami caused severe damage. Design: This was a retrospective cohort study. Setting: The study was conducted at university and children's hospitals in Miyagi Prefecture. Participants: The annual and monthly numbers of infants born with CL/P were obtained from medical records. The affected period of birth was defined as 1 year from December 1, 2011, to November 30, 2012. The control period was 5 years from January 1, 2006, to December 31, 2010. The annual and monthly numbers of births in Miyagi Prefecture were obtained using e-Stat, which is a portal for Japanese government statistics. Main Outcome Measures: Main outcome measures were birth prevalence of CL/P during the control and affected periods. Results: There were no significant differences between the control and affected periods in the prevalence (per 10 000 live births) of cleft lip with or without palate (13.8 vs 16.7; P = .342), isolated cleft palate (5.2 vs 3.2; P = .267), or overall CL/P (19.0 vs 19.9; P = .799). Conclusions: We did not observe that the 2011 Tōhoku earthquake and tsunami affected the birth prevalence of CL/P in Miyagi Prefecture, even though it severely impacted human health in the area.